Politisasi Identitas dalam Pemilu: Tinjauan Politik Hukum dan Prinsip Maqāṣid Al-Sharīʿah terhadap Ketahanan Nasional - Latifa, Dwi Ria (STAINI Press, 2025)
Indonesia as a multicultural democratic country faces vulnerability to identity political mobilization, especially those rooted in primordial issues such as religion and ethnicity. This phenomenon was prominent in the 2017 Jakarta Regional Election and the 2019 Presidential Election, which showed the increasing social polarization due to digital disinformation and SARA-based campaigns. This situation is a threat to national resilience, as well as showing the insynchronity between the constitutional principle of non-discrimination and the weak campaign regulations in Law No. 7 of 2017. This study uses a mixed approach between normative and empirical. The normative approach is used to analyze the political, legal and regulatory aspects of election campaigns, while the empirical approach is carried out through field studies using data triangulation techniques from official documents, NGO reports, and digital campaign archives. The results of the study show three main findings: (1) The ambiguity of the definition of